The Television Audience In Batu Pahat: A Study Of Viewers’ Characteristics And Viewing Patterns - Leu, Siew Ying (Universiti Sains Malaysia, 1982)
This is a descriptive study of Tv audience in Batu Pahat. (Batu Pahat is a town in Johore where TV viewers can view programmes from TV Malaysia as well as TV Singapore.) It will try to describe who these viewers are. The extent that viewers are exposed to more channels and therefore their viewing habits as well as whether ‘spillover’ has any effects on the viewers.